Subchronic toxicity test of Strychnos ligustrina extract and dihydroartemisinin-piperaquine phosphate in male and female mice - Siti Sadiah, Wasrin Syafii, Rita Kartika Sari, Yulvian Sani, Hamzah Alfarisi, Haula Fadya Andini, Roro Iyaka Nuraliyu, Umi Cahyaningsih (Journal of Applied Pharmaceutical Science, 2023)
Strychnos ligustrina extract and dihydroartemisinin-piperaquine phosphate (SL+DHP) may increase antimalarial potential. However, no research reported the toxic effect of SL+DHP. Therefore, this study investigated the subchronic toxicity of SL+DHP in male and female mice for 28 days. Subchronic toxicity tests were using National Agency of Drug and Food Control test guidelines. Mortality, bodyweight, and relative organ weight were measured. Blood samples were analyzed for hematological and biochemical parameters. Organs were examined for histopathological analysis. The highest mortality in mice was because of high doses (800 + 333 mg/kg BW) in male and female mice. The high dose significantly decreased body weight for 28-day treatments but increased after stopping administration for 2 weeks. The relative organ weight showed a significant change in the kidney, brain, and gonad of treatment groups, but its change was a recovery in satellite groups. Strychnos ligustrina extract+DHP in the high dose significantly changed the hematological and biochemical parameters of treatment groups, but these changes recovered in male and female mice of satellite groups. Histopathological examination revealed that S. ligustrina extract+DHP had a strong toxic effect in the kidney and caused ulcer compared to other organs. Subchronic toxicity of SL+DHP for 28 days was safe in low doses (200 + 111 mg/kg BW). Medium doses (400 + 222 mg/kg BW) and high doses(800 + 333 mg/kg BW) showed a toxic effect but recovered after stopping administration for 2 weeks.